2016
DOI: 10.1186/s40902-016-0082-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes of lip morphology following mandibular setback surgery using 3D cone-beam computed tomography images

Abstract: BackgroundThe aims of this study are to evaluate the lip morphology and change of lip commissure after mandibular setback surgery (MSS) for class III patients and analyze association between the amount of mandibular setback and change of lip morphology.MethodsThe samples consisted of 14 class III patients treated with MSS using bilateral sagittal split ramus osteotomy. Lateral cephalogram and cone-beam CT were taken before and about 6 months after MSS. Changes in landmarks and variables were measured with 3D s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Seung et al evaluated the lip morphological changes following mandibular setback surgery using 3D cone-beam computed tomography images. Their results revealed that both upper and lower lip areas on frontal-view images were not signi cantly changed, but the upper lip area on the lateral view increased, and the lower lip area decreased 33 , which corresponded to our research ndings that in the frontal view, both A and B areas showed no signi cant changes after surgery.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Seung et al evaluated the lip morphological changes following mandibular setback surgery using 3D cone-beam computed tomography images. Their results revealed that both upper and lower lip areas on frontal-view images were not signi cantly changed, but the upper lip area on the lateral view increased, and the lower lip area decreased 33 , which corresponded to our research ndings that in the frontal view, both A and B areas showed no signi cant changes after surgery.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the variables were chosen after a review of various articles on factors affecting smile esthetics. 16,17,24,32 In particular, we measured the lip height ratio, lip asymmetry, and lip area, 33 which crucially affect smile esthetics but are usually neglected in smile analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors assessed Ch movement in 2 directions (posteriorly and inferiorly) after isolated mandibular setback surgery. 2,[14][15][16] All these studies demonstrated that mandibular setback surgery caused the Ch to move posteriorly, simultaneous with inferior movement of the upper lip. The circular orbicularis oris muscle may cause this posterior movement of the Ch, along with that of the upper and lower lips.…”
Section: Discussionmentioning
confidence: 97%
“…Peak et al evaluated the changes in lip morphology following mandibular setback in class III patients [20]. They demonstrated that the frontal view of the lip area did not change significantly after surgery.…”
Section: Discussionmentioning
confidence: 99%